PENGKAJIAN PENERAPAN EKOWISATA DI ELEPHANT SAFARI PARK DESA TARO KABUPATEN GIANYAR (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2015)
The Elephant Safari Park as the research location is based on existence of interaction between tourist and society; the usage of the society area as tourism attraction; beside that are raised of some complaints from tourists and society toward elephant dirt, and clean water, etc. The aims of this research is researching the application of ecotourism principles. The data in this research are collected through observation, interview and documentation. The informants in this research consist of leaders of society, general manager and operational manager of Elephant Safari Park. The data is analysed by descriptive qualitative. The results of this study show that the application of ecotourism principle in Elephant Safari Park was done based on natural tourism, sustainable tourism development and accommodate local culture, mean while conservational action activities, educational aspect and local economy have not totally applied the ecotourism principle yet. Generally, ecology aspect has not surely known it negative impact yet, but it able to give small impact to the environment, from the economy aspect give benefit the society, but don’t totally involved. Meanwhile from the social culture aspect, also give benefit to the local society, but are raised of the anxiety for the future. The suggestion that is taken from the research, the management of Elephant Safari Park cooperated with the village of Taro and supported by government need to improve contribution toward action of conservation, involved and education of society. For further research is needed depth research concerning existence of Elephant Safari Park toward carrying capacity, connection between the existence of elephant with conservation of white buffalo, and exact effort for conservation of white buffalo.